Case Study of Counter Pressure Therapy and Five Finger Hypnosis to Reduce Pain Intensity and Anxiety in the First Stage of Labor - Diyah Ayu Prameswari; Surtiningsih; Yanti, Linda (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Childbirth is a process that begins with uterine contractions, followed by the opening of the cervix, birth of the baby, and expulsion of the placenta. During this process, mothers often experience pain and anxiety. One way to deal with pain is with the counter pressure technique, which is a massage using the fist that provides constant pressure on the spine during contractions. Additionally, increased anxiety can worsen pain during labor. One method that can be used to manage anxiety is five-finger hypnosis, a form of self-hypnosis that can create deep relaxation, thereby reducing tension and stress. This study aims to assess the reduction in pain and anxiety in five mothers who are in the first stage of labor after receiving counter pressure therapy and five finger hypnosis. The methods used include SOP for counter pressure, five finger hypnosis, observation sheets, Wong-Baker pain scale, and STAI anxiety scale. The results showed a reduction in pain and anxiety after the intervention, indicating that counter pressure therapy and five finger hypnosis were effective in reducing pain and anxiety during the first stage of labor.